2020
DOI: 10.1523/jneurosci.1755-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Prior Cocaine Use Alters the Normal Evolution of Information Coding in Striatal Ensembles during Value-Guided Decision-Making

Abstract: Substance use disorders (SUDs) are characterized by maladaptive behavior. The ability to properly adjust behavior according to changes in environmental contingencies necessitates the interlacing of existing memories with updated information. This can be achieved by assigning learning in different contexts to compartmentalized "states." Though not often framed this way, the maladaptive behavior observed in individuals with SUDs may result from a failure to properly encode states because of drug-induced neural a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Importantly, the OFC, a key area of dysfunction in OCD (Chamberlain et al 2008;Remijnse et al 2006), is implicated in representing states (Schuck et al 2016;Wilson et al 2014). In extension of this framework, it should be noted that SUD, where high stimulus stickiness has been observed (Kanen et al 2019), may be characterised by over-encoding of state-specific rules and information (Mueller et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the OFC, a key area of dysfunction in OCD (Chamberlain et al 2008;Remijnse et al 2006), is implicated in representing states (Schuck et al 2016;Wilson et al 2014). In extension of this framework, it should be noted that SUD, where high stimulus stickiness has been observed (Kanen et al 2019), may be characterised by over-encoding of state-specific rules and information (Mueller et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, trial-type information reflects the odor-reward contingencies in a task block. Statistical inference revealed that the decoding accuracies for MSN and FSI pseudo-ensembles from the cocaine group were significantly higher than those from the sucrose group in some trial phases, suggesting that prior cocaine use increases the amount of rewardrelated information being encoded by the pseudo-ensembles (Mueller et al, 2021).…”
mentioning
confidence: 94%
“…Behavioral flexibility is typically assessed using reversal learning tasks, in which subjects learn to perform a specific action to receive a reward, then must alter their behavior when a different action is rewarded instead (Izquierdo et al, 2017). Impairments in such flexibility are observed in substance use disorder, characterized by persistent drug use despite negative outcomes (Mueller et al, 2021). Individuals with substance use disorders may choose to use drugs even when more rewarding alternatives are available especially in contexts that were previously associated with drug use.…”
mentioning
confidence: 99%
See 2 more Smart Citations